2021
DOI: 10.2147/dddt.s322702
|View full text |Cite
|
Sign up to set email alerts
|

Orally Deliverable Dual-Targeted Pellets for the Synergistic Treatment of Ulcerative Colitis

Abstract: Purpose The effective treatment of ulcerative colitis (UC) poses substantial challenges, and the aetiopathogenesis of UC is closely related to infectious, immunological and environmental factors. Currently, there is a considerable need for the development of orally bioavailable dosage forms that enable the effective delivery of therapeutic drugs to local diseased lesions in the gastrointestinal tract. Methods Berberine (BBR) and Atractylodes macrocephala … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…As reported, the cyclodextrin inclusion approach can prevent volatile oil from being oxidated and breaking down, while it can also convert the liquid medicine into a powder to improve the drug's stability during both preparation and storage operations [39]. Tang et al developed stomach-targeted AO pellets for the synergistic treatment of UC [40]. In addition, Weiwei Shi et al created a microemulsion of cinnamon essential oil to address its quick disintegration and oxidation vulnerabilities [41].…”
Section: Discussionmentioning
confidence: 99%
“…As reported, the cyclodextrin inclusion approach can prevent volatile oil from being oxidated and breaking down, while it can also convert the liquid medicine into a powder to improve the drug's stability during both preparation and storage operations [39]. Tang et al developed stomach-targeted AO pellets for the synergistic treatment of UC [40]. In addition, Weiwei Shi et al created a microemulsion of cinnamon essential oil to address its quick disintegration and oxidation vulnerabilities [41].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that YJP-A and (or) its main active ingredients have potential regulatory effects on some points in ILC3s-TD IgA-colonic mucosal flora axis. For instance, our previous studies have shown that YJP could reduce IgA levels in serum ( Zhang et al, 2018 ) and the expression of ileal and colonic mucosal SIgA in Large Intestine Dampness-heat Syndrome ( Yao et al, 2019 ); berberine, the active component of Coptidis Rhizoma and Phellodendri Chinensis Cortex , and paeoniflorin, a main ingredient of Paeoniae Radix Alba , could enhance immune function by lowering IgA levels ( Li et al, 2012 ; Tang et al, 2021 ); baicalin, a main ingredient of Scutellaria baicalensis , regulates intestinal flora through promoting the production of SCFAs and further protects dysfunction of intestinal mucosal immune ( Hu et al, 2021b ); baicalein ameliorates UC by improving intestinal epithelial barrier via AhR/IL-22 pathway in ILC3s ( Li et al, 2021 ); Huangqin decoction exerted therapeutic effect on UC mice by increasing the proportion of ILC3s and MHC II expression to suppress the function of Th17 and Th1 cells and promote Treg and Th2 cells ( Zhou et al, 2021 ); curcumin and paeoniflorin could ameliorate UC by regulating gut microbiota ( Huang et al, 2017 ; Fan et al, 2020 ). Therefore, the combination of these medicines, YJP-A could ameliorate DSS-induced UC in mice by regulating ILC3s-TD IgA-colonic mucosal flora axis ( Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that BBR has a long history in Chinese medicine used as an antibacterial agent to treat dysentery, it is promising to repurpose BBR for UC and other inflammatory-associated diseases. Tang and coworkers have recently demonstrated in a rodent model that oral administration of BBR effectively alleviates animals’ colitis symptoms when combined with another Chinese herb Atractylodes macrocephala Koidz ( 24 ). The underlying mechanisms involve local- and systemic regulations of the immune system, including the reduced pro-inflammatory cytokines IL-4, IL-6, IL-1β, TNF-α, and myeloperoxidase (MPO), and IgA, IgG levels.…”
Section: Introductionmentioning
confidence: 99%